Two‐Dimensional Metal–Organic Framework Nanosheets. Issue 1 (29th December 2016) - Zhao, Meiting; Lu, Qipeng; Ma, Qinglang; Zhang, Hua
Abstract : Two‐dimensional (2D) metal–organic framework (MOF) nanosheets are attracting increasing research interest due to their unique properties originating from their ultrathin thickness and large surface area with highly accessible active sites. Here, the aim is to provide recent advances in the synthesis of 2D MOF nanosheets by using the top‐down and bottom‐up methods, including sonication exfoliation, interfacial synthesis, three‐layer synthesis, and surfactant‐assisted synthesis methods. In addition, the recent progress in 2D‐MOF‐nanosheet‐based nanocomposites is also introduced. The synthesis of 2D MOF nanosheets should lead to new kinds of functional nanomaterials for a wide range of applications. Abstract : Recent advances in the synthesis of 2D metal–organic framework (MOF) nanosheets using the top‐down and bottom‐up methods are summarized, including sonication exfoliation, interfacial synthesis, three‐layer synthesis, and surfactant‐assisted synthesis methods. In addition, the recent progress in 2D‐MOF‐nanosheet‐based nanocomposites is also introduced.